Management Strategies for Homestays in Pancoh Tourism Village, Turi, Sleman - Wigati, Erna; Winarno, Susilo Budi; Sugiama, Aceng Gima; Kustini, Henny (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2025)
This article aims to understand the strategies in homestay management, the challenges faced, and the solutions implemented by the managers in the homestay management in Pancoh tourist village. The method used in this research is a descriptive qualitative method by conducting observations, documentation, and interviews with the Chairman of Pokdarwis, the manager of the tourist village, and the homestay manager in the Pancoh ecotourism village. The results of this research are strategies for managing homestays by managing physical and environmental aspects, human resource and institutional aspects, and promotional aspects. The challenge faced in managing the Homestay is the large amount of waste that appears when tourists live in. The solution implemented by the manager is the application of a one-stop management system.